Educational Management Information System: Integration of Technology and Management to Support Organizational Efficiency - Syahril, Sulthan (Global Education Journal, 2025)
The rapid development of information technology highlights the importance of understanding Management Information Systems (MIS) in supporting the efficiency and effectiveness of organizational decision-making. This study aims to explain the basic concepts of MIS, its components, and its benefits in a management context. This study uses a qualitative approach through a literature review of various relevant journals and books. The research findings indicate that MIS is an integration of people, machines, procedures, and information technology designed to produce quality information. MIS not only improves the quality of managerial decisions but also accelerates workflow and improves overall organizational performance. By understanding MIS thoroughly, organizations can more easily adapt to change and remain competitive.